2015
DOI: 10.1111/eth.12403
|View full text |Cite
|
Sign up to set email alerts
|

Warning Signal Efficacy: Assessing the Effects of Color, Iridescence, and Time of Day in the Field

Abstract: Warning coloration deters predators from attacking distasteful or toxic prey. Signal features that influence warning color effectiveness are not well understood, and in particular, we know very little about how effective short-wavelength and iridescent colors are as warning color elements in nature and how warning signal effectiveness changes throughout the day. We tested the effect of these factors on predation risk in nature using specimens of the distasteful pipevine swallowtail butterfly, Battus philenor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
(200 reference statements)
0
8
1
Order By: Relevance
“…The combination of red and black elements is a textbook example of aposematic coloration (Endler and Mappes 2004), but the monotonous metallic colouration was as effective as light red-and-black pattern in our experiments in terms of predator avoidance learning and signal memorability. A metallic lustre is generally interpreted as a warning signal (Borer et al 2010), but studies of bird responses to iridescence are scarce and the findings are contradictory: some, including our study, have demonstrated that iridescence itself enhances avoidance learning, (Fabricant et al 2014;Waldron et al 2017) while others have reported no effects of prey iridescence on bird attack rates (Pegram et al 2015). This discrepancy may indicate that bird responses to iridescent coloration of prey are idiosyncratic.…”
Section: Chemical Defence Of C Lapponica Against Bird Predatorscontrasting
confidence: 81%
“…The combination of red and black elements is a textbook example of aposematic coloration (Endler and Mappes 2004), but the monotonous metallic colouration was as effective as light red-and-black pattern in our experiments in terms of predator avoidance learning and signal memorability. A metallic lustre is generally interpreted as a warning signal (Borer et al 2010), but studies of bird responses to iridescence are scarce and the findings are contradictory: some, including our study, have demonstrated that iridescence itself enhances avoidance learning, (Fabricant et al 2014;Waldron et al 2017) while others have reported no effects of prey iridescence on bird attack rates (Pegram et al 2015). This discrepancy may indicate that bird responses to iridescent coloration of prey are idiosyncratic.…”
Section: Chemical Defence Of C Lapponica Against Bird Predatorscontrasting
confidence: 81%
“…More crosses, including backcrosses to disentangle genetic effects on melanism, orange and blue coloration, together with additional experiments with bird predators, would be needed to better estimate the relative importance of black, orange, and blue for the mimetic function. Experiments both in the laboratory and the field on the possible importance of orange and blue coloration for aposematism in B. philenor have shown that orange and blue both contribute to aposematism (Pegram et al 2013) or that orange possibly contributes more (Pegram et al 2015). Considering our experiments, melanism appears to be the dominating component of the B. philenor warning signal.…”
Section: Discussionmentioning
confidence: 47%
“…) or that orange possibly contributes more (Pegram et al. ). Considering our experiments, melanism appears to be the dominating component of the B. philenor warning signal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations